The impact of reformed missions on the origin, growth and identity of the Reformed Church of East Africa, 1905-2000 - Van Zyl, Jacobus,1962- (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2001.